2017
DOI: 10.1111/cns.12719
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical features and mutation spectrum in Chinese patients with CADASIL: A multicenter retrospective study

Abstract: These findings broaden the mutational and clinical spectrum of CADASIL and provide additional evidences for the existence of founder effect in CADASIL patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 34 publications
4
61
3
Order By: Relevance
“…In other cohorts that studied populations of similar ages, the suspicion based on the clinical‐radiological characterization was similar, with higher frequency of adult‐onset vanishing white matter disease, and other pathologies such as leukodystrophy with ovarian failure related to the mutation in the AARS2 gene, which we did not have in our series (Lynch et al., ). The sequence of the NOTCH3 gene confirmed the diagnosis in only four of the patients studied with suspected CADASIL, unlike other reports where the diagnostic yield was higher (Chen et al., ). In our particular case, we recognize the laxity in the selection criteria, as we studied those patients who met at least one clinical and one radiological criterion described by Davous () without being strict in the sum of 15 or more points on the diagnostic probability scale of CADASIL proposed by Pescini, Nannucci, & Pantoni (), there is a better performance in the molecular study of the NOTCH3 gene.…”
Section: Discussioncontrasting
confidence: 78%
“…In other cohorts that studied populations of similar ages, the suspicion based on the clinical‐radiological characterization was similar, with higher frequency of adult‐onset vanishing white matter disease, and other pathologies such as leukodystrophy with ovarian failure related to the mutation in the AARS2 gene, which we did not have in our series (Lynch et al., ). The sequence of the NOTCH3 gene confirmed the diagnosis in only four of the patients studied with suspected CADASIL, unlike other reports where the diagnostic yield was higher (Chen et al., ). In our particular case, we recognize the laxity in the selection criteria, as we studied those patients who met at least one clinical and one radiological criterion described by Davous () without being strict in the sum of 15 or more points on the diagnostic probability scale of CADASIL proposed by Pescini, Nannucci, & Pantoni (), there is a better performance in the molecular study of the NOTCH3 gene.…”
Section: Discussioncontrasting
confidence: 78%
“…The confluent white matter hyperintensities as well as multiple lacunar infarcts shown on brain MRI scanning of our patients were in accordance with typical neuroimaging features of CADASIL. None of the patients in present study reported a history of migraine with or without aura, which is consistent with a relatively low frequency of migraine in patients of CADASIL from Asian countries [16,17]. The diagnosis of CADASIL was genetically confirmed by the detection of a homozygous mutation in exon 11 of NOTCH3 gene, which was predicted to cause a substitution of arginine with cysteine (p.R587C) in the encoded receptor.…”
Section: Discussionsupporting
confidence: 85%
“…Patients who exhibit agnogenic white matter abnormality, unexplained spastic paraparesis, or early‐onset dementia were suggestive of leukodystrophies . Firstly we screened causative genes for CADASIL, adrenoleukodystrophy, hereditary spastic paraplegia (HSP), and familial Alzheimer's disease (FAD) on these patients in our previous studies, and patients who carry pathogenic variants were excluded. Then, 28 unrelated patients (probands) were recruited consecutively between March 2015 and August 2018 from the Department of Neurology in Second Affiliated Hospital of Zhejiang University School of Medicine.…”
Section: Methodsmentioning
confidence: 99%